Perceived Job Autonomy in the Manufacturing Sector: Effects of Unions, Gender, and Substantive Complexity - Kirmeyer, Sandra L.; Shirom, Arie (Academy of Management Journal, 1986)
In this article the authors discusses research they conducted that examined the amount of perceived and actual job autonomy experienced by both male and female union and non-union employees. The author hypothesized that non-union employees would perceive more autonomy than union employees and that male union members would perceive more autonomy than female union members. Their reasoning for these beliefs were based in the knowledge that unions are more concerned with issues such as employee wages and hours of work than with issues related to job satisfaction such as decision making responsibilities. The author believed that men would experience more autonomy than women due to the fact that women are overrepresented in low wage positions that do not grant them much autonomy anyway.